Application of macroalgal biomass derived biochar and bioelectrochemical system with Shewanella for the adsorptive removal and biodegradation of toxic azo dye. (February 2021) - Gurav, Ranjit; Bhatia, Shashi Kant; Choi, Tae-Rim; Choi, Yong-Keun; Kim, Hyun Joong; Song, Hun-Suk; Lee, Sun Mi; Lee Park, Sol; Lee, Hye Soo; Koh, Joonseok; Jeon, Jong-Min; Yoon, Jeong-Jun; et al.
Abstract: The present study aimed towards adsorptive removal of the toxic azo dye onto biochar derived from Eucheuma spinosum biomass. Characterization of the produced biochar was performed using X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), and Brunauer-Emmett-Teller (BET). Eucheuma spinosum biochar (ES-BC) produced at 600 °C revealed a maximum adsorption capacity of 331.97 mg/g towards reactive red 120 dye. The adsorption data fitted best to the pseudo-second order kinetics (R 2  > 0.99) and Langmuir isotherm (R 2  > 0.98) models. These adsorption models signified the chemisorption mechanism with monolayer coverage of the adsorbent surface with dye molecules. Furthermore, the adsorption process was mainly governed by electrostatic interaction, ion exchange, metal complexation, and hydrogen bonding as supported by the solution pH, FTIR, XPS, and XRD investigation. Nevertheless, alone adsorption technology could not offer a complete solution for eliminating the noxious dyes. Therefore, the bioelectrochemical system (BES) equipped with previously isolated marine Shewanella marisflavi BBL25 was intended for the complete remediation of azo dye. The BES II demonstrated highest dye decolorization (97.06%) within 48 h at biocathode where the reductive cleavage of the azo bond occurred. Cyclic voltammetry (CV) studies of the BES revealed perfect redox reactions taking place where the redox mediators shuttled the electrons to the dye molecule to accelerate the dye decolorization. Besides, the GC-MS analysis revealed biotransformation of the dye into less toxic metabolites as tested using a phyto and cytogenotoxicity. Graphical abstract: Image 1 Highlights: Macroalgae derived biochar showed excellent performance for azo dye adsorption. Pseudo-second order and Langmuir isotherm were the best suited adsorption model. Shewanella marisflavi BBL25 attained >97% dye decolorization at biocathode. Cyclic voltammetry revealed direct and mediator driven electron transfer mechanism. This study provides a suitable and sustainable approach for remediation of azo dyes.